Preparation and evaluation of pectin beads - (:unkn) unknown (ELSEVIER SCIENCE BV, 1996)
Pectin beads were prepared by dropping drug-containing solutions of pectin into calcium chloride solutions. The droplets instantaneously formed gelled spheres by ionotropic gelation. Atenolol (cationic) and piroxicam (anionic) were used as model drugs. By using this method, beads with high drug contents were obtained. The effect of formulation and processing factors was also studied.
Keywords: beads; pectin; ionotropic gelation; Atenolol; piroxicam; sustained-release; DRUG